The effect of ultrasound-assisted enzymatic hydrolysis (UAEH) on the physicochemical properties and bioactivity of edible swiftlet’s nest hydrolysates - Nita Kusumawati; Pirim Setiarso; Sunu Kuntjoro; Ita Fatkhur Romadhoni; Gina Noor Djalilah; Khofifatul Rahmawati; Senja Salzanabila Putri Perdana; Achmad Naufal Al Hafidl; Amirul Mu’minin; Safira Keysa Dewayanti; Anandatya Ramdhan Achmad Al Manfaluty; Shafira Basri; Nailah Clarinta Artanti; Firnanda Amelia Wulandari; Aprilia Putri Nur Afifatun Nisak; Muhammad Zaky Fachriansyah (Communications in Science and Technology, 2026)
This study investigates the effect of ultrasound-assisted enzymatic hydrolysis (UAEH) compared with non-hydrolyzed samples on the physicochemical properties and bioactivity of edible swiftlet’s nest (ESN) co-product hydrolysates using bromelain under optimized processing conditions. ESN was subjected to UAEH treatment (40 °C, pH 7.0, 40 kHz) followed by freeze-drying. The results showed that hESN-C achieved the highest yield (62.13%) and degree of hydrolysis (37.95%), while hESN-CP gave the lowest (28% yield, 9.57% degree of hydrolysis). FTIR spectroscopy confirmed the retention of key glycoprotein functional groups across all hydrolysate fractions: characteristic O–H/N–H stretching vibrations at 3270-3272 cm-1, Amide I at 1630-1631 cm-1, and Amide II at 1526-1537 cm-1, together with glycan-associated C–O/C–N stretching vibrations, indicating selective peptide bond cleavage by bromelain without disruption of glycosidic linkages and preservation of the carbohydrate architecture in the resulting bioactive glycopeptides. HPLC qualitatively confirmed sialic acid retention in all fractions (retention time 6-7 min). Amino acid profiling revealed complete essential amino acid profiles in all samples, with the highest concentrations in hESN-C dominated by L-valine (36,507.33 mg/kg), L-proline (37,083.32 mg/kg), and L-serine (37,635.48 mg/kg). Fatty acid analysis identified oleic acid (0.1491%) and linoleic acid (0.0428%) as the predominant unsaturated fatty acids, particularly in hESN-CP. Particle size analysis demonstrated that UAEH produced smaller, more uniformly distributed nanoparticles (14.17-27.03 nm) with low polydispersity indices (<0.3). Scanning electron microscopy revealed distinct morphological differences: hESN-C and hESN-D exhibited homogeneous laminar structures, whereas hESN-CP displayed heterogeneous porous morphology attributed to keratin from feather residues. UAEH treatment significantly increased soluble protein content (hESN-C: 1.246 μg/μL; hESN-CP: 0.844 μg/μL) and DPPH radical scavenging activity (up to 10.70% for hESN-CP) relative to non-hydrolyzed controls. Heavy metal concentrations (Hg: 0.0172–0.0236 mg/L; Cd: 0.1194–0.1444 mg/L; Pb: 0.11–1.4 mg/L) remained within Chinese safety thresholds, and water activity was reduced to safe levels (<0.60). Collectively, these results demonstrate that UAEH is an effective and sustainable strategy for valorizing ESN co-products into physicochemically improved, bioactive glycopeptide hydrolysates with potential as functional food ingredients. Future studies employing quantitative in vitro bioactivity assays and in vivo validation are warranted to substantiate broader health-benefit claims.